AN ANALYSIS OF STUDENT ENGLISH-INDONESIA TRANSLATION OF TWO ROBERT FROST'S POETRIES(A CASE STUDY OF STUDENT IN A TRANSLATION CLASS AT THE ENGLISH EDUCATION DAPARTEMENT OF FPBS UPI) - JAYANTI, Indah (2010)
This research investigates how twelve students in a translation class at the English Education Department of FPBS UPI translate two English poetries by Robert Frost into Indonesian. Two main points examined include the strategies applied and the problems encountered by the students in translating poetries. By using a qualitative method with case study design, the data were collected through documents of the poetries and questionnaires. Through a textual descriptive analysis, they were classified and analyzed by using Lefevere's theory of poetry translation strategies (1975) and Hariyanto's theory concerning problems in translating poetry (2003). The findings reveal that the strategy mostly applied in translating the poetries is literal (75.8%). Nevertheless, 22.7% of the literal translation applied mixed strategies: literal and rhymed, literal and free-verse as well as literal and phonemic. Besides, the linguistic problems (54.5%) are mostly encountered by the students. To solve the problems encountered, the students applied different strategies. It indicates that the strategies applied in translating poetries are adjusted to the need of the poetries and the choice of the translator. Thus, this research concludes that there is no best strategy in poetry translation, but strategy which is appropriate for the context of the poetry should be applied.